Menstrual Cycle Disturbances after COVID-19 Vaccination: A Cross-Sectional Study - Farima Rahimi Mansour; Amirreza Keyvanfar; Hanieh Najafiarab; Shaghayegh Hooshmand Chayijan; Farah Farzaneh; Golnoush Mortezaei (International Journal of Fertility and Sterility, 2024)
Background: Following COVID-19 vaccination, some women suffered from menstrual cycle disturbances. This studyaimed to investigate menstrual cycle disturbances after COVID-19 vaccination in women of reproductive age.Materials and Methods: This cross-sectional study was performed on 407 vaccinated women in the vaccinationcenter of Imam Hossein Hospital (Tehran, Iran) between October 2021 and October 2022. They were interviewedbased on a research-made checklist which consisted of two areas of questions about the baseline characteristics of participantsand menstrual cycle characteristics to explore menstrual characteristics following COVID-19 vaccination.Results: The prevalence of menstrual disturbances was higher after the third dose (38.3%) compared with the second(27.9%) and first (17.7%) doses (P<0.001). After the first dose, a history of polycystic ovarian syndrome [PCOS, oddsratio (OR)=7.35, 95% confidential interval (CI)= (3.64-14.82), P<0.001] and menstrual disturbances with unknownetiology [OR=15.23, 95% CI=(6.30-36.80), P<0.001] could predict menstrual disturbances. After the second dose, ahistory of menstrual disturbances with unknown etiology [OR=3.83, 95% CI=(1.47-9.94), P=0.006] and menstrualdisturbances after the first dose [OR=201.96, 95% CI= (40.99-994.90), P<0.001] were predictors of menstrual disturbances.After the third dose, a history of menstrual disturbances with unknown etiology [OR=3.09, 95% CI=(1.00-9.52), P=0.048], menstrual disturbances after the first [OR=9.82, 95% CI=(1.38-69.69), P=0.022] and second[OR=7.83, 95% CI=(1.46-41.92), P=0.016] doses could predict menstrual disturbances.Conclusion: We detected that many women experienced various menstrual disturbances after vaccination against SARS-CoV-2(severe acute respiratory syndrome coronavirus 2). Furthermore, a history of menstrual abnormalities (before COVID-19 vaccinationand following the previous doses of these vaccines) was associated with developing menstrual disturbances.